Minority and Majority Faculty Members in a Historically Black College/University: Redefining Professors' Teacher Credibility and Classroom Management. Issue 1 (1st January 2016) - Wei, Fang-Yi Flora; Hendrix, Katherine Grace
Abstract : When African American professionals become the majority (e.g., historically Black colleges and universities—HBCUs), whether they and White professors would perceive different challenges in class is unknown. Qualitative findings revealed that White professors considered their professional image as "well-learned" and "intelligent" in the HBCU, whereas African American professors perceived their credibility as dependent on their work experience. In addition, the "call response" communication strategy and classroom tardiness were two cultural shocks encountered by White professors. However, unlike PWIs, the HBCU culture facilitated students' use of professional titles when addressing White and African American female participants.